2021
DOI: 10.1177/1090198120986782
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Relationship Between Exercise, Sleep, and Mood in Young Adults

Abstract: Insufficient sleep is a serious public health problem in college students. Exercise is a widely prescribed behavioral treatment for sleep and mood issues; however, more focused and gender-specific prescriptions are needed. The present study examined relationships between exercise, sleep, and mood in undergraduate men and women. Students ( N = 866, 19.6 ± 1.4 years, 38.7% women) were recruited from campus recreation facilities and completed demographic, the Pittsburgh Sleep Quality Index, mood (Patient-Reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 86 publications
(90 reference statements)
3
17
1
Order By: Relevance
“…Similarly, in the study, we also found the effect of exercise intensity on sleep quality, that is, the higher the exercise intensity, the better the improvement effect of sleep quality, and there was a significant dose-response effect. However, the Glavin's study pointed out that exercise frequency had an impact on sleep quality, and gender factors can also affect sleep quality [38], which was contrary to the conclusion drawn in this paper that exercise frequency did not lead to improved sleep quality. The main reason for the different results from this study may be the different exercise methods used, which caused the deviation of the results.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, in the study, we also found the effect of exercise intensity on sleep quality, that is, the higher the exercise intensity, the better the improvement effect of sleep quality, and there was a significant dose-response effect. However, the Glavin's study pointed out that exercise frequency had an impact on sleep quality, and gender factors can also affect sleep quality [38], which was contrary to the conclusion drawn in this paper that exercise frequency did not lead to improved sleep quality. The main reason for the different results from this study may be the different exercise methods used, which caused the deviation of the results.…”
Section: Discussioncontrasting
confidence: 99%
“… 1 Insufficient sleep is a serious public health problem in college students. 2 It is generally considered that chronotype is one of an expression of circadian rhythm. 3 The most common methods of classification used in chronotype is morning-types (M-types), neutral-types (N-types) and evening-types (E-types).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, when dividing the sample by gender, it is important to mention that equestrian sport is a female-dominated sport ( Burbage and Cameron, 2018 ) and this is evident in the distribution of the sample in our study. Regarding the perceived benefits of horseback riding, there are no significant differences in four of the five dimensions, possibly conditioned by the differences in sample size, since in other sports disciplines there are significant differences ( Speck and Harrell, 2003 ; Vlachopoulos et al, 2013 ; Glavin et al, 2021 ). Only social contact is rated higher among men, as in other studies ( Craft et al, 2014 ; van Uffelen et al, 2017 ; Blanco et al, 2019 ).…”
Section: Discussionmentioning
confidence: 90%